Lipid profile alterations in non-infectious uveitis: correlation with quantitative optical coherence tomography angiography parameters - Lei Feng; Guangming Qin; Junhui Shen (BMJ Open Ophthalmology)
Background/aims Lipid profiles have been changed in numerous chronic conditions. The impact of uveitis on lipid metabolism remains unclear.Methods This is a cross-sectional study included 416 patients with non-infectious uveitis (NIU) and 416 healthy subjects. Standard techniques were used to measure total cholesterol (TC), triglycerides (TG), high-density lipoprotein-cholesterol (HDLc), low-density lipoprotein-cholesterol (LDLc) levels. Quantitative optical coherence tomography angiography (OCTA) parameters were obtained from 500 eyes in each group. Correlation analysis examined the relationship between lipid profile and OCTA parameters.Results Patients with NIU exhibited significantly elevated TC, TG and LDLc levels compared with controls (p=0.003; p<0.001; p<0.001, respectively). Subgroup analysis revealed that HDLc was significantly lower in Behçet’s disease (p=0.024) compared with controls. Vascular density (VD) in the superficial capillary plexus (SCP), deep capillary plexus (DCP), choriocapillaris and optic disk were significantly decreased in NIU eyes (p<0.05, respectively) compared with controls. HDLc exhibited a significant negative correlation with VDs in the whole and parafovea SCP (r=−0.489, p=0.008; r=−0.480, p=0.0026, respectively), while LDLc showed a significant positive correlation with VDs in the whole and parafovea DCP in NIU patients (r=0.576, p=0.032; r=0.267, p=0.034, respectively).Conclusions The lipid profile is altered in NIU, and there are correlations between HDLc and LDLc levels and VD as measured by OCTA. Lipid profile analysis may offer valuable insights into evaluating vascular and metabolic aspects of NIU.